Parental Engagement Approaches to Primary School Children ' s Literacy Skills Development in Tabora Region, Tanzania - Nyang ' anyi, Mariam John; Bhalalusesa, Eustella Peter (Papers in Education and Development, 2023)
This paper employs a qualitative case study design to explore parental engagement approaches in developing children ' s literacy skills in primary schools. Focus group discussions and semi-structured interviews were used with purposive sampling to obtain 44 participants. It was revealed that parents in high-performing schools were highly engaged in their children ' s literacy development through regular parent-teacher communications, parent-teacher trust, and parent-teacher cooperation. Parents in lowperforming schools, on the other hand, were less engaged due to the lack of awareness of their children ' s literacy skills development and hectic schedules on socio-economic activities. The paper recommends that teachers use encouraging and friendly approaches to parents so that they can feel comfortable engaging in developing their children ' s literacy skills. Keywords: high-performing schools, literacy skills, low-performing schools, parental engagement approaches, parent-teacher communication